Geographic reconstruction of a Central-West Brazilian landscape devastated during the first half of the 20th century: Mato Grosso de Goiás (Sustainability in Debate, 2018)
In the history of humanity, there are various accounts of ecosystems that were devastated to the detriment of scientific knowledge. In Brazil, the Atlantic Forest and Cerrado biomes are emblematic of this phenomenon. Specifically, within the latter, an environment consisting predominantly of savanna, a large tropical forest enclave existed, known as Mato Grosso de Goiás. This ecosystem was almost devastated by the Brazilian land expansion policies during the first half of the 20th century. The objective of this study is to estimate the extent of the original area of the Mato Grosso de Goiás ecosystem through integration of historical and cartographic data using geoprocessing techniques. The original area was estimated around 26,391 km². These data can aid in the planning of conservation policies for the Cerrado biome. In addition, the used methodology can be adapted to similar studies, especially in the field of environmental science.